Type II Bi1 − xWxO1.5 + 1.5x: a (3 + 3)‐dimensional commensurate modulation that stabilizes the fast‐ion conducting delta phase of bismuth oxide. Issue 6 (1st December 2015) - Wind, Julia; Auckett, Josie E.; Withers, Ray L.; Piltz, Ross O.; Maljuk, Andrey; Ling, Chris D.
Abstract : The Type II phase in the Bi1 − x W x O1.5 + 1.5 x system is shown to have a (3 + 3)‐dimensional modulated δ‐Bi2 O3 ‐related structure, in which the modulation vector ɛ `locks in' to a commensurate value of 1/3. The structure was refined in a 3 × 3 × 3 supercell against single‐crystal Laue neutron diffraction data. Ab initio calculations were used to test and optimize the local structure of the oxygen sublattice around a single mixed Bi/W site. The underlying crystal chemistry was shown to be essentially the same as for the recently refined (3 + 3)‐dimensional modulated structure of Type II Bi1 − x Nb x O1.5 + x (Ling et al., 2013), based on a transition from fluorite‐type to pyrochlore‐type via the appearance of W4 O18 `tetrahedra of octahedra' and chains of corner‐sharing WO6 octahedra along 〈110〉F directions. The full range of occupancies on this mixed Bi/W site give a hypothetical solid‐solution range bounded by Bi23 W4 O46.5 ( x = 0.148) and Bi22 W5 O48 ( x = 0.185), consistent with previous reports and with our own synthetic and analytical results.